Current Drifts in Business and Finance - Aishwarya Paradeshi; K.V.N Lakshmi (East Asian Journal of Multidisciplinary Research, 2022)
Business and finance go hand in hand together. Without finance, the business can’t go anywhere. It needs finance for capital, leasing, equipment, etc. For business, finance plays a vital role in its expansion, diversification, and overall growth of the business. Business and finance are growing day by day by adopting innovations and technologies. In recent years we can see that their wide number of changes in finance and business.  This paper will study recent trends in business and finance like digitization, cryptocurrency, green finance, artificial intelligence in business, and other aspects.